Successful treatment of refractory palmoplantar pustulosis by upadacitinib: report of 28 patients - Du, Na; Yang, Jingyi; Zhang, Yiwen; Lv, Xinyan; Cao, Lei; Min, Wei (Frontiers in Medicine, 2024)
Background: Upadacitinib, a specific JAK1 inhibitor, has minimal effect on other JAK subtypes. It influences the inflammatory process in various ways. Upadacitinib has been approved for conditions such as rheumatoid arthritis, psoriatic arthritis, atopic dermatitis, and ulcerative colitis in various countries. The purpose of this study is to assess the clinical efficacy and safety of upadacitinib in patients with refractory palmoplantar pustulosis who have not responded to conventional treatments(e.g.Acitretin, Tripterygium wilfordii Hook F, cyclosporine, methotrexate).We conducted a retrospective collection of clinical data from 28 patients who received upadacitinib treatment at the